Coating in primary reformer’s radiant section - Baskara Aji Nugraha (Jurnal Rekayasa Proses, 2013)
Kaltim Parna Industri, (KPI), experienced severe fouling on the flue gas side of the coil heat exchangers. This happened on the outer tube side, which some were finned tubes. Although the cause had not clearly been identified, laboratory analysis indicated that the fouling had similar composition with the firebrick. Therefore, preliminary assumption of what causes the problem was firebrick erosion that was carried away by flue gas flow.In order to completely eliminate fouling source and hopefully to reduce cleaning frequency, we planned to coat combustion chamber with special high temperature resistance coating.The result was promising that the material was stable against high temperature and even further helped the operation.